Provincializing Empire: Ōmi Merchants in the Japanese Transpacific Diaspora - Jun Uchida (University of California Press, 2023)
Provincializing Empire explores the global history of Japanese expansion through a regional lens. It rethinks the nation-centered geography and chronology of empire by uncovering the pivotal role of expeditionary merchants from Ōmi (present-day Shiga Prefecture) and their modern successors. Tracing their lives from the early modern era, and writing them into the global histories of empire, diaspora, and capitalism, Jun Uchida offers an innovative analysis of expansion through a story previously untold: how the nation's provincials built on their traditions to create a transpacific diaspora that stretched from Seoul to Vancouver, while helping shape the modern world of transoceanic exchange. “Provincializing Empire offers a stimulating and persuasive account of the longue durée of Japanese capitalist development, connecting Japanese historiography to important conversations on the history of racial capitalism and geographies of space, place, and scale.” — DAVID AMBARAS, author of Japan's Imperial Underworlds: Intimate Encounters at the Borders of Empire “Wide-ranging yet richly documented, Provincializing Empire offers a powerful new transregional history of Japanese capitalism, challenging claims about the developmental state. It tells the fascinating story of a merchant diaspora whose growth was entwined with Japanese imperialism, and of the invented traditions that sustained provincial identity amid global commercial expansion.” — JORDAN SAND, author of Tokyo Vernacular: Common Spaces, Local Histories, Found Objects ""A tour de force! Jun Uchida's lucid narrative illuminates the multidirectional movements of settler-migrant merchants from peripheral Japan that cut across the prescribed borders of empires and nation-states. Empirically rich and theoretically sophisticated, Provincializing Empire calls into question many assumptions about Japanese imperialism and offers a less spatially bounded story of grassroots expansionism."" — EIICHIRO AZUMA, author of In Search of Our Frontier: Japanese America and Settler Colonialism in the Construction of Japan's Borderless Empire ""Provincializing Empire is a wonderfully creative model for connecting local and global history. Uchida frames her stimulating account of Japanese overseas commercial expansion, colonialism, and diaspora not as the top-down story of state policy but as the local history of a mercantile community."" — DAVID L. HOWELL, Robert K. and Dale J. Weary Professor of Japanese History, Harvard University"
Keywords: 300; merchants; Japan; Japanese Transpacific Diaspora